2003
DOI: 10.1212/01.wnl.0000091864.39702.1c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognition in Parkinson’s disease

Abstract: The SCOPA-COG is a short, reliable, and valid instrument that is sensitive to the specific cognitive deficits in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
239
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(261 citation statements)
references
References 35 publications
14
239
0
8
Order By: Relevance
“…These functions that emerged as being affected partially resemble the pattern of subcortical dementia as defined by some authors, although the visuospatial functions refer more to the cortical level [3, 24]. Thus, the pattern of cognitive decline in PDD patients may differ from that in AD patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These functions that emerged as being affected partially resemble the pattern of subcortical dementia as defined by some authors, although the visuospatial functions refer more to the cortical level [3, 24]. Thus, the pattern of cognitive decline in PDD patients may differ from that in AD patients.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported that the cognitive functions affected by PDD were attention, the working memory, and the executive and visuospatial functions, whereas verbal functions, thinking and reasoning were relatively spared [23, 24]. These functions that emerged as being affected partially resemble the pattern of subcortical dementia as defined by some authors, although the visuospatial functions refer more to the cortical level [3, 24].…”
Section: Discussionmentioning
confidence: 89%
“…Currently, emotional incontinence is associated with multi-infarct dementia, but not mixed dementia (Moroney et al, 1997). The so called sub cortical dementias, like dementia in Parkinson´s disease, display visual hallucinations and the impairment of memory and executive functions (Marinus et al, 2003, Galvin et al, 2006, and are associated with patient age and not related to disease duration (Mayeux et al, 1992). The differential cognitive features that distinguish fronto-temporal dementia from Alzheimer´s disease include a relative preservation of drawings and calculation performance (Mendez et al, 1996), abilities that could interfere in the interpretation of some structured cognitive tests for determining capacity.…”
Section: Competency Impairment and Incapacity In Older Peoplementioning
confidence: 99%
“…The SCOPA-COG is an instrument which was designed to assess the specific cognitive deficits found in Parkinson`s disease (Marinus et al, 2003). The scale consisting of 10 items covers the domains: memory and recall (verbal recall, digit span backward, indicate cubes), attention (counting backward, months backward), executive function (fist-edge-palm, semantic fluency, dice), visual-spatial functions (assembly pattern) and memory (delayed recall).…”
Section: B: Scopa-cog(scales For Outcome Of Parkinson`s Disease-cognimentioning
confidence: 99%